A highly potent extended half-life antibody as a potential RSV vaccine surrogate for all infants - Zhu, Qing; McLellan, Jason S; Kallewaard, Nicole L; Ulbrandt, Nancy D; Palaszynski, Susan; Zhang, Jing; Moldt, Brian; Khan, Anis; Svabek, Catherine; McAuliffe, Josephine M; Wrapp, Daniel; Patel, Nita K; et al. (Science translational medicine, 2017)
Prevention of respiratory syncytial virus (RSV) illness in all infants is a major public health priority. However, no vaccine is currently available to protect this vulnerable population. Palivizumab, the only approved agent for RSV prophylaxis, is limited to high-risk infants, and the cost associated with the requirement for dosing throughout the RSV season makes its use impractical for all infants. We describe the development of a monoclonal antibody as potential RSV prophylaxis for all infants with a single intramuscular dose. MEDI8897*, a highly potent human antibody, was optimized from antibody D25, which targets the prefusion conformation of the RSV fusion (F) protein. Crystallographic analysis of Fab in complex with RSV F from subtypes A and B reveals that MEDI8897* binds a highly conserved epitope. MEDI8897* neutralizes a diverse panel of RSV A and B strains with >50-fold higher activity than palivizumab. At similar serum concentrations, prophylactic administration of MEDI8897* was ninefold more potent than palivizumab at reducing pulmonary viral loads by >3 logs in cotton rats infected with either RSV A or B subtypes. MEDI8897 was generated by the introduction of triple amino acid substitutions (YTE) into the Fc domain of MEDI8897*, which led to more than threefold increased half-life in cynomolgus monkeys compared to non-YTE antibody. Considering the pharmacokinetics of palivizumab in infants, which necessitates five monthly doses for protection during an RSV season, the high potency and extended half-life of MEDI8897 support its development as a cost-effective option to protect all infants from RSV disease with once-per-RSV-season dosing in the clinic.